The Role of Transport Technologies in Children's Road Safety and Traffic Education - Camplin, Tjaša; Živković, Sašo; Marič, Miha (Prometna varnost v lokalnem okolju: problemsko-učno sodelovanje z Intermatic d.o.o., 2026)
This chapter addresses road safety with a focus on the role of modern traffic monitoring and information systems and their importance for child safety in kindergartens and schools. The aim of the study was to examine how technology, infrastructure, and traffic education are interconnected and how different stakeholders (educators, parents, kindergarten management, local communities, and experts) perceive their effectiveness in everyday traffic practice. The theoretical part is based on a systematic literature review covering road safety, traffic education, behavioral factors, and the use of intelligent transport systems. The empirical part is based on a qualitative study conducted using semi-structured interviews. The findings indicate that participants recognize the important role of technology in improving safety; however, they emphasize that the key factor remains proper traffic education and cooperation between institutions. The results highlight the need for a holistic approach combining education, infrastructure, and technological solutions. Overall, the findings suggest that integrating these elements effectively can significantly contribute to reducing traffic risks and improving long-term traffic safety culture.